PERANCANGAN KALKULASI BIAYA PRODUKSI DI USAHA CIPTA MANDIRI - Prakoso, Aryo; Wardhaningrum, Oktaviani Ari (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2019)
Kesilir Village, Wuluhan District, Jember Regency is one of the villages that is expected to have village independence. The main program for developing cooperation between Universitas Jember and local villages through thematic KKN programs is the development of tourism villages and prosperous entrepreneurs. One of the independent businesses in this village is Usaha Cipta Mandiri, a home industry that is engaged in furniture manufacturing. The products produced are heterogeneous and can be tailored to the needs of consumers. The products produced are furniture, chairs, tables, cabinets, door leaves, shutters and so on. Usaha Cipta Mandiri serves consumers from around the city in the Besuki Residency. Even though the entrepreneur has the tagline What You Order We Do, in accordance with the wishes of the client, this business still has a fundamental weakness in its business, namely a cost management system that is not measured and recorded. Solutions offered by the above problems, through the collaboration of the University of Jember service team and the involvement of students with Cipta Usaha Mandiri partners, by designing accounting records in a simple way using Microsoft Excel program. The target of this activity is accounting software manufacturing with Microsoft Excel platform. Keywords: independence, production costs, manufacturing accounting